Meet the Puritans : with a guide to modern reprints - Beeke, Joel R, 1952-; Pederson, Randall J. 1975- (Grand Rapids : Reformation Heritage Books, 2006)
Puritan literature has so multiplied that few book lovers can afford to purchase all that is being republished. What books should one buy? Where can one find a brief summary of each Puritan work and a brief description of the author? This guide answers these questions by providing a brief biography of each Puritan author whose works have been reprinted since 1956 and a short review of those books. We hope this will help purchasers of Puritan books, interest other readers in the Puritans, and guide those already immersed in Puritan literature to further depths of study.
Includes bibliographical references (p. [861]-888) and index.
Keywords: Puritans